THE DEVELOPMENT OF LKPD INTEGRATED SCIENCE BASED ON PROBLEM BASED LEARNING (PBL) OF THE INTEGRATED CRITICAL THINGKING SKILL ON THE TOPIC PRESSURES OF SUBTANCES FOR JUNIOR HIGH SCHOOL - Cici Ramadani; Tuti Lestari (Universe, 2020)
The 2013 curriculum was developed with several updates, including student-centered learning and critical thinking learning. Science learning in SMP / MTs in 2013 Curriculum is carried out in an integrated manner in accordance with Permendikbud No.35 Year 2018. This study aims to develop Integrated Science Learning Unit based on Integrated Problem Based Learning based on critical thinking for grade VIII SMP / MTs and reveal the level of validity and practicality from the developed LKPD. The type of research used is Research and Development (R&D) using a 4-D model consisting of four stages, they are the Define, Design, Develop, and Dessiminate step. But the dessiminate stage is not carried out due to time and cost limitations. LKPD validated by 3 lecturers of Natural Sciences Faculty of Mathematics and Natural Sciences UNP using a validation sheet instrument. The practicality test was conducted by 2 science teachers and 30 students of 24 Padang Middle School using a practicality sheet instrument. Based on research conducted obtained LKPD in the category of very valid with a value of 92.85%, and practical categories LKPD with a value of 88.46% according to the teacher's assessment and 88.90% according to the student's assessment.